2008
DOI: 10.1242/jcs.022640
|View full text |Cite
|
Sign up to set email alerts
|

Isoform B of myosin II heavy chain mediates actomyosin contractility during TNFα-induced apoptosis

Abstract: fibroblasts, indicating the participation of MHCIIB in these events. Moreover, inhibition of atypical PKCζ, which targets MHCIIB but not MHCIIA, blocked TNFα-induced shrinkage and detachment in TtT/GF cells and wild-type fibroblasts, but the inhibitory effect was significantly reduced in MHCIIB -/-fibroblasts. TNFα treatment increased cytoskeleton-associated myosin light chain (MLC) phosphorylation but did not induce actin cleavage. In conclusion, our results demonstrate that MHCIIB, together with MLC phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Finally, the death of a cell also involves contractility that affects several aspects of cell death at both the structural and molecular levels, such as release of nuclear RanGTP, compaction and entosis (Moss et al, 2009;Overholtzer et al, 2007;Smadja-Lamere et al, 2008;Solinet and Vitale, 2008).…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…Finally, the death of a cell also involves contractility that affects several aspects of cell death at both the structural and molecular levels, such as release of nuclear RanGTP, compaction and entosis (Moss et al, 2009;Overholtzer et al, 2007;Smadja-Lamere et al, 2008;Solinet and Vitale, 2008).…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…Communal et al (43) have reported that β-adrenergic stimulation via norepinephrine exposure in adult rat ventricular cardiomyocytes triggered a caspase 3 targeting of α-actin, α-actinin, and cardiac troponin T before the onset of apoptosis. More recently, other sarcomeric proteins have been shown to be direct caspase targets in apoptotic models including, myosin heavy chain and ventricular myosin light chain (44)(45)(46). The ability of caspase 3 to directly modify cellular structure while altering the activity of key gene expression programs implies that this protease (and the intrinsic pathway) may serve as a fulcrum for agonistinduced hypertrophy in general.…”
Section: Activation Of the Intrinsic Cell Death Pathway Is Required Formentioning
confidence: 99%
“…The specificity of these antibodies has been shown elsewhere (Solinet and Vitale 2008). Mouse monoclonal anti-cortactin (clone 4F11), polyclonal anti-Par3 and goat polyclonal anti-vimentin were from Chemicon (Temecula, CA, USA).…”
Section: Source Of Antibodies and Chemicalsmentioning
confidence: 99%
“…Pre-cleared supernatants (2 mg protein/ml) were incubated with either buffer (control) or with the immunoprecipitating antibody overnight at 4°C on an orbital rocker. One hundred microlitre of protein A Sepharose 4B beads, pre-washed with PBS, were added to each sample and the mixtures were further incubated for 4 h at 4°C (Solinet and Vitale 2008). Beads were rinsed several times in lysis buffer, and were finally resuspended in 30 ll electrophoresis sample buffer and boiled for 5 min.…”
Section: Coimmunoprecipitation Studiesmentioning
confidence: 99%
See 1 more Smart Citation